ENERGY OF THE FUTURE: THE ROLE OF BIOGAS AND BIOMETHANE IN UKRAINE’S SUSTAINABLE DEVELOPMENT - OSTRA, NATALIA; MALOGULKO, JULIYA; СІКОРСЬКА, ОЛЕНА; TEPTIA, VIRA; POVSTIANKO, KATERYNA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The biogas and biomethane industries are increasingly serving as a pillar of Ukraine’s energy independence, as they enable a reduction in fossil fuel imports and increase the resilience of the national energy system. This study analyzes the country’s biomethane potential, gas production and purification technologies, economic and regulatory conditions, and prospects for entering the EU market. Calculations show that Ukraine can generate over 10 billion m³ of biomethane annually from agricultural, livestock, food, and municipal waste. Key biogas upgrading methods—membrane separation, PSA, and cryogenic distillation—are reviewed and their effectiveness assessed. The regulatory framework is gradually approaching EU standards, but still requires full harmonization. A comparative cost analysis has shown that Ukrainian biomethane is competitive due to cheaper raw materials, although development is hampered by a lack of subsidies, a lack of feedstock, and complex certification procedures. At the same time, biomethane allows you to reduce CO₂ emissions by 85% compared to natural gas and plays an important role in the circular economy. The dynamics of 2019–2024 demonstrate a gradual increase in production, but Ukraine still lags behind the leading EU countries. Successful exports require modernization of the gas transportation system, balancing standards and overcoming logistical barriers. The results obtained form a comprehensive basis for effective state policy that can unlock the full potential of the biomethane industry in Ukraine. The study confirmed that the biogas and biomethane sector is key to Ukraine’s energy independence and decarbonization. Law No. 1820-IX on the development of biomethane and the electronic register of guarantees of origin lay the foundation for exports, but the rules need to be fully aligned with the RED II Directive and the EU Regulation on guarantees of origin.